Multibeam bathymetry processed data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM31, Yermak Plateau, Arctic Ocean - Jensen, Laura; Hadler, Annette; Hoffmann, Jasper; Gebhardt, Andrea Catalina; Dreutter, Simon; Dorschel, Boris; Geissler, Wolfram H (PANGAEA, 2025)
Multibeam data were collected during RV Maria S. Merian cruise MSM31 (2013-08-17 to 2013-09-18). Multibeam sonar system was Kongsberg EM 122 multibeam echosounder. Data are processed with Caris HIPS, including sound velocity correction with SV data from CTDs and World Ocean Atlas 18 (https://www.ncei.noaa.gov/archive/accession/NCEI-WOA18), tidal correction with TPXO9_atlas_v5 (https://www.tpxo.net/global/tpxo9-atlas), and manual cleaning. The soundings are combined in daily files, the format is XYZ ASCII (<Lon> <Lat> <Depth in meters, positive up, relative to mean sea level>). Additional grids have been computed with depth dependent cell size to visualize the data. These grids are not meant for scientific analysis or navigation, but for overview purposes only.
Keywords: Arctic Ocean; Bathymetry; EM122; Maria S. Merian; Multibeam; Yermak Plateau